Kritik Terhadap Pemikiran al-Albani Tentang Kehujjahan Hadis Ḍa‘īf - Kudhori, Muhammad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2017)
Assessment the quality of ḥadīṡ is an ijtihād tradition which is carried out by experts of ḥadīṡ. Evidently, despite the experts of ḥadīṡ have agreed to determine the validity of ḥadīṡ, in some cases, they divided in assessing the quality of ḥadīṡ. The valuation differences will impact the mining law of this ḥadīṡ. At the level of practice, the experts of ḥadīṡ also have a different argument in the ability to use ḍa‘īf ḥadīṡ. Al-Albānī is one of a contemporary theologian of ḥadīṡ who reject the practice of ḍa‘īf ḥadīṡ absolutely. The reason is ḍa‘īf ḥadīṡ only provide virtue and al-marjūḥ (alleged weak), so he thought that set an action with ḍa‘īf ḥadīṡ is a tashrī‘, while tashrī‘ cannot use ḍa‘īf ḥadīṡ. He also claimed that the ban to practice ḍa‘īf ḥadīṡ is the opinion of the experts of ḥadīṡ such as al-Bukhārī, Muslim, Ibn Ma‘īn, Ibn Ḥazm and Ibn al-‘Arabī. But in reality, based on the data that has been presented, the experts are actually practicing ḍa‘īf ḥadīṡ to faḍā’il al-a‘māl and its kind in their books. These facts, of course, dismissed the claims made by al-Albānī saying that they refuse to practice ḍa‘īf ḥadīṡ absolutely. It became evident that the stronger opinion is the opinion of the majority of experts who were allowed, even encourage the practice of ḍa‘īf ḥadīṡ to fada'ilal-a'mal and its kind with the conditions that have been set.